2008
DOI: 10.1016/j.bone.2008.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY (PYY) levels and bone mineral density (BMD) in women with anorexia nervosa

Abstract: Introduction-Anorexia nervosa is a psychiatric illness that results in significant bone loss. Studies examining the neuroendocrine dysregulation that occurs in AN may increase understanding of endocrine systems that regulate bone mass. PYY is an anorexigenic peptide derived primarily from the intestine, with actions mediated via activation of Y-receptors. We have previously shown that PYY levels are elevated in adolescents with AN. Y2 receptor knockout mice have increased bone mineral density (BMD) and thus PY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 34 publications
12
57
0
Order By: Relevance
“…PYY has also been shown to play a role in bone homeostasis and may be involved peripherally in the regulation of bone formation through osteoblastic Y1 receptors. Elevated PYY levels have been shown to correlate with diminished BMD in women with anorexia nervosa, a condition that results in significant bone loss [36]. However, analysis of a PYY knockout line found that a lack of PYY led to an osteopenic phenotype with reductions in vertebral cancellous bone mass and bone strength [37].…”
Section: Discussionmentioning
confidence: 99%
“…PYY has also been shown to play a role in bone homeostasis and may be involved peripherally in the regulation of bone formation through osteoblastic Y1 receptors. Elevated PYY levels have been shown to correlate with diminished BMD in women with anorexia nervosa, a condition that results in significant bone loss [36]. However, analysis of a PYY knockout line found that a lack of PYY led to an osteopenic phenotype with reductions in vertebral cancellous bone mass and bone strength [37].…”
Section: Discussionmentioning
confidence: 99%
“…Other hormonal alterations that contribute to low bone density and lower levels of bone formation markers include low levels of leptin and insulin, and high levels of PYY [31,35]. In women with AN, mean overnight PYY levels correlated negatively with bone density at multiple skeletal sites, and at the spine PYY was a major determinant of bone density variability [69]. …”
Section: Bone Metabolismmentioning
confidence: 99%
“…After correction for BMI in patients with anorexia nervosa, PYY is negatively correlated with areal and estimated volumetric BMD, and negatively correlated with biochemical markers of bone formation and resorption [104,105]. This seems to contradict the PYY knockout model.…”
Section: Peptide Yymentioning
confidence: 56%